2022
DOI: 10.3390/biomedicines10040819
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical and Genetic Features of ALS in the Last Decade: A Prospective Population-Based Study in the Emilia Romagna Region of Italy

Abstract: Increased incidence rates of amyotrophic lateral sclerosis (ALS) have been recently reported across various Western countries, although geographic and temporal variations in terms of incidence, clinical features and genetics are not fully elucidated. This study aimed to describe demographic, clinical feature and genotype–phenotype correlations of ALS cases over the last decade in the Emilia Romagna Region (ERR). From 2009 to 2019, our prospective population-based registry of ALS in the ERR of Northern Italy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Traditionally, ALS has always been considered a disastrous disease that afflicts motor neurons and leads to devastating immobility whilst cognition remains intact [ 27 ]. This assumption has been debunked in recent years with numerous studies that have demonstrated the presence of cognitive and behavioral dysfunctions in ALS [ 6 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In particular, an association between ALS and FTD has been increasingly recognized, and with the advent of new genetic discoveries [ 29 , 30 ], as well as new neuropathological and neuroimages evidence, the concept of the frontotemporal dementia–motor neuron disease continuum has progressively emerged.…”
Section: Cognitive Impairment and The Frontotemporal Dementiamentioning
confidence: 99%
See 3 more Smart Citations
“…Traditionally, ALS has always been considered a disastrous disease that afflicts motor neurons and leads to devastating immobility whilst cognition remains intact [ 27 ]. This assumption has been debunked in recent years with numerous studies that have demonstrated the presence of cognitive and behavioral dysfunctions in ALS [ 6 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In particular, an association between ALS and FTD has been increasingly recognized, and with the advent of new genetic discoveries [ 29 , 30 ], as well as new neuropathological and neuroimages evidence, the concept of the frontotemporal dementia–motor neuron disease continuum has progressively emerged.…”
Section: Cognitive Impairment and The Frontotemporal Dementiamentioning
confidence: 99%
“…In particular, an association between ALS and FTD has been increasingly recognized, and with the advent of new genetic discoveries [ 29 , 30 ], as well as new neuropathological and neuroimages evidence, the concept of the frontotemporal dementia–motor neuron disease continuum has progressively emerged. Five population-based studies have explored the presence of cognitive impairment and frontotemporal dementia–motor neurons ( Table 3 ) [ 6 , 31 , 32 , 33 , 34 ]. Evidence has shown that patients with ALS may present executive dysfunction, personality changes, poor insight, obsessions, aggressiveness, irritability and verbal fluency alteration.…”
Section: Cognitive Impairment and The Frontotemporal Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the mutations affect the C-terminal glycin-rich domain of the protein [ 3 , 4 ]. Phenotypically, TARDBP mutations are associated with a wide range of clinical manifestations [ 5 ], including cases with slow, medium, and fast disease progression [ 6 ], bulbar or upper limb onset, with or without cognitive and/or behavioral impairment [ 7 ]. The frequency and kind of TARDBP mutations are not homogeneous among different populations with higher frequency in Southern Europe (up to three times higher, especially in France and in Italy) than in other Caucasian populations [ 8 ] where an additional founder effect for A382T mutation has been described in Sardinia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%